ANALYSIS OF THE INFLUENCE OF CULTURE, SOCIAL, PERSONAL AND PSYCHOLOGICAL FACTORS ON CONSUMER DECISIONS IN BUYING BANCASSURANCE INSURANCE PRODUCTS (CASE: BRI LIFE BRANCH OF PAMULANG BRANCH, SOUTH TANGERANG CITY) - Arya Pradhana Fadjari Putra; Djumarno (Dinasti Publisher, 2020)
The purpose of this study is to develop a comprehensive model by measuring the influence of cultural, social, personal and psychological on consumer decisions in purchasing decisions for bancassurance. This research applies a descriptive research design using survey methods. Sampling uses convinient sampling as a sampling technique. This study uses the structural equation modeling approach - Lisrel to test the influence of the significance of the overall model and predetermined pathway. The findings show that cultural and social factors have a positive relationship but do not have a significant effect on purchasing decisions for bancassurance. Further findings show that personal and psychological factors have a positive relationship and have a significant influence on purchasing decisions for bancassurance.